2020
DOI: 10.1080/2162402x.2020.1724763
|View full text |Cite
|
Sign up to set email alerts
|

Helper T cell-dominant tertiary lymphoid structures are associated with disease relapse of advanced colorectal cancer

Abstract: Tertiary lymphoid structures (TLSs), clusters of immune cells found around tumor tissue, have been shown to be associated with anti-tumor immunity, but the cellular composition within each TLS and whether the cellular composition of a TLS affects a patient's prognosis are poorly understood. In the present study, each TLS was categorized according to its cellular composition determined by a system of multiplex immunohistochemical staining and quantitative analysis, and the correlation between the category and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…While the presence of TLS often positively impacts clinical outcomes, TLS composition itself might dictate treatment efficacy, tumor recurrence and patient survival. Indeed, Yamaguchi and colleagues 156 classified TLS into five categories based on their immune cell composition and found that TLS enriched in helper T cells were associated with disease relapse in advanced colorectal cancer. Another example is the diversity found among ASC where IgA producing cells are almost exclusively associated with a poor prognosis, while IgG + secreting cells frequently correlated with increased patient survival.…”
Section: Future Perspectives and Outstanding Questionsmentioning
confidence: 99%
“…While the presence of TLS often positively impacts clinical outcomes, TLS composition itself might dictate treatment efficacy, tumor recurrence and patient survival. Indeed, Yamaguchi and colleagues 156 classified TLS into five categories based on their immune cell composition and found that TLS enriched in helper T cells were associated with disease relapse in advanced colorectal cancer. Another example is the diversity found among ASC where IgA producing cells are almost exclusively associated with a poor prognosis, while IgG + secreting cells frequently correlated with increased patient survival.…”
Section: Future Perspectives and Outstanding Questionsmentioning
confidence: 99%
“…A large number of studies demonstrated that the tumor microenvironment is closely related to the prognosis and effectiveness of immunotherapy [45][46][47]. TLS is a crucial component of tumor immune microenvironment [5,48], which not only facilitating the recruitment of immune cells or play an anti-tumor role, but also act as a predictor for the prognosis of various cancer [4,7,10,15,22,24,34,39]. However, several studies reported the effect of TLS expression on prognosis and clinicopathological characteristics of solid tumor patient remains controversial [9,11,13,15].…”
Section: Discussionmentioning
confidence: 99%
“…B cells could be involved in the formation of TLS by producing CXCL13 and lymphotoxin [ 50 , 52 ], and also in the maturation of an antitumoral humoral response in the TME [ 50 ]. TLS have been reported in various types of cancers including lung, breast, pancreas, colorectal, and oral cancer [ 53 , 54 ]. These structures have been associated with positive prognostic value in some tumors [ 55 , 56 ], such as high-grade serous ovarian cancer, where tumor infiltration by CD8 + T cells only showed prognostic value when it was combined with the presence of TLS and a high count of plasma cells, CD4 + T cells and CD20 + B cells [ 56 ].…”
Section: Discussionmentioning
confidence: 99%